THE INFLUENCE OF WORK CONFLICT ON EMPLOYEE PERFORMANCE AT CLASS I CIPINANG STATE DETENTION CENTER - Ansyah, Alif Aldi; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the influence of work conflict on employee performance at Class I Cipinang State Detention Center. The research was conducted in response to the growing recognition that work conflict, if managed well, can have a positive impact on performance. The purpose of this study is to explore how various dimensions of work conflict, such as task conflict, relationship conflict, and process conflict, affect employee productivity and well-being. Using a quantitative research method, data were collected from employees to gain insight into their perceptions of work conflict and its impact on their performance. The analysis revealed that moderate levels of work conflict are perceived positively by employees and contribute to higher performance, especially when they are managed effectively within teams. The findings indicate a significant positive relationship between work conflict and employee performance, suggesting that conflict, when properly addressed, can enhance productivity. Keywords: Work Conflict; Employee Performance; Qualitative Research